Hydrosurgical debridement as an approach to wound healing: an animal thermal burn model. (2nd May 2019) - Hirokawa, Eiko; Sato, Tomoya; Fujino, Takashi; Gotoh, Yoshiya; Yokogawa, Hideki; Ichioka, Shigeru
Abstract : Objective: This study investigates the advantages of hydrosurgical debridement compared with surgical debridement. Method: Thermal skin burns were created on the backs of male Wistar rats. Surgical debridement was used to treat one wound and hydrosurgical debridement (Versajet Hydrosurgery System, Smith&Nephew, UK) used to treat the second wound. Debridement time, blood loss volume, time-to-heal and histologic changes in the wound areas were compared. Results: A total of 23 rats were used in the study. Debridement time and time-to-heal were significantly shorter with hydrosurgical debridement than with surgical debridement (p<0.01 and p<0.05, respectively). Blood loss volume was significantly less with hydrosurgical debridement (p<0.01), and the wound surface area was significantly smaller on days two (p<0.01), four (p<0.05) and seven (p<0.05). Dense inflammatory cell infiltration into dermal muscle was deeper after surgical debridement (p=0.017). Reactive fibrotic tissue at the wound surface was significantly thinner (p<0.001) and the vascular endothelial cell count was significantly higher (p<0.001) after hydrosurgical debridement. Conclusion: The hydrosurgical system used appears to provide for minimally invasive debridement that can be performed in a relatively short period of time. Use of the device appears to minimise injury to healthy tissue and ameliorate inflammation, which in turn promotes early wound healing and reduces scar contracture. Hydrosurgical debridement appears to cause less damage to normal tissues. Furthermore, it is easier and requires less time.